2011
DOI: 10.1111/j.1365-2559.2011.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

High incidences of DNA ploidy abnormalities in tongue squamous cell carcinoma of young patients: an international collaborative study

Abstract: Young patients with TSCC represent a distinct clinical entity. The high incidence of DNA ploidy abnormalities suggest that they may have increased genomic instability and indicates underlying genetic differences between TSCC in young and older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 46 publications
(104 reference statements)
3
68
1
6
Order By: Relevance
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
“…As for sample size, the number of participants ranged from 10 to 2,223 young subjects, as described in Table 1. Age distribution of patients varied: individuals considered young were those aged 18-39 years (7,8,10,11) (23.5%), < 30 years (13,20) (3,6,8,9,(11)(12)(13)(14)(16)(17)(18)(19)(20)(21) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En 2005, Mason et al [28] ont confirmé l'étude de Bill et al [27] en montrant que les syndromes de Li-Fraumeni et de Bloom et l'anémie de Fanconi étai-ent associés à une forte incidence des cancers de la langue du fait de l'atteinte systématique des télomères. La forte incidence d'aneuploidie et les détections importantes d'anomalies de ploïdies chez les sujets de moins de 40 ans supportent l'hypothèse que la prédisposition génétique et l'instabilité chromosomique favoriseraient les cancers buccaux chez les sujets jeunes [29]. …”
Section: Infection Viraleunclassified
“…[2][3][4][5][6][7][8][9][10] Various attempts have been made to automate this diagnostic process of nuclear DNA content assessment using computeraided analysis of two-dimensional (2-D) slides. [9][10][11] Currently, the two most common techniques used to quantify DNA content are flow cytometry (FCM) and 2-D image cytometry (ICM). In FCM, the sample is stained with a DNA specific fluorophore [usually diamidino-2-phenylindole (DAPI)]; the cells rapidly flow one-by-one across the focused laser beam and the intensities of the fluorescences emitted are used to quantify the DNA content.…”
Section: Introductionmentioning
confidence: 99%